Purification of Derivatized Oligosaccharides by Solid Phase Extraction for Glycomic Analysis - Zhang, Qiwei; Li, Henghui; Feng, Xiaojun; Liu, Bi-Feng; Liu, Xin (PLOS ONE, 2014)
Profiling of glycans released from proteins is very complex and important. To enhance the detection sensitivity, chemical derivatization is required for the analysis of carbohydrates. Due to the interference of excess reagents, a simple and reliable purification method is usually necessary for the derivatized oligosaccharides. Various SPE based methods have been applied for the clean-up process. To demonstrate the differences among these methods, seven types of self-packed SPE cartridges were systematically compared in this study. The optimized conditions were determined for each type of cartridge and it was found that microcrystalline cellulose was the most appropriate SPE material for the purification of derivatized oligosaccharide. Normal phase HPLC analysis of the derivatized maltoheptaose was realized with a detection limit of 0.12 pmol (S N−1 = 3) and a recovery over 70%. With the optimized SPE method, relative quantification analysis of N-glycans from model glycoproteins were carried out accurately and over 40 N-glycans from human serum samples were determined regardless of the isomers. Due to the high stability and sensitivity, microcrystalline cellulose cartridge showed potential applications in glycomics analysis.